Lost (and Found) in Translation : Evaluating English translations of Mulan Shi - Miao, Yan; Zlatev, Jordan (Public Journal of Semiotics, 2024)
The classical Chinese poem Mulan Shi has been translated many times into different languages and adapted to different media. Drawing upon Sonesson’s definition of translation as a double act of communication and combining it with concepts from narratology and translation theory, we develop a framework comprising three levels of translation resemblance: (a) between the structure and content of the source and target texts, (b) stylistic resemblance, and (c) pragmatic resemblance, concerning the impacts of the texts upon respective audiences. We compare five English translations of the poem, selecting the one by Arthur Waley from 1923 for detailed scrutiny. We triangulate between a first-person, second-person and third-person methods, leveraging our intuitive grasp of languages and cultures, and measures of different aspects in the source and target texts. To be able to assess pragmatic resemblance we conducted a survey with 20 participants from each cultural/linguistic group (Chinese and Western English speakers), asking for interpretations and evaluations of key aspects of the poem. The findings were that the target text exhibits high resemblance with respect to narrative structure but moderate resemblance on content due to some key omissions and substitutions. The stylistic resemblance was also moderate, while the pragmatic was considerable, with similar assessments in the two groups, though with different proportions.
Keywords: cognitive semiotics; cross-cultural communication; descriptive phenomenology; narratology; poetry; translation theory